2018
DOI: 10.1007/s10035-017-0778-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of combined slip and finite sliding at spherical grain contacts

Abstract: The present paper is aimed at developing the analytical description of the interaction of two contacting spheres for several classes of slip and sliding trajectories, typical in the experimental testing. The analysis accounts for memory effects in the slip regime and configurational effects in the sliding regime, expressed in terms of an active loading surface and memory surfaces within the space of contact forces. Analytical relations for contact response are derived for linear and piecewise-linear motion tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Previous works (Balevicius & Mroz, ; Cavarretta et al, ; Nardelli et al, ; Nardelli & Coop, ; Sandeep & Senetakis, , ) showed that the theoretical curves plotted using the Hertz model fit the experimental data reasonably well apart from an initial regime where the behavior is elastic‐plastic to plastic for rough surface morphologies.…”
Section: Contact Mechanics Modelsmentioning
confidence: 78%
“…Previous works (Balevicius & Mroz, ; Cavarretta et al, ; Nardelli et al, ; Nardelli & Coop, ; Sandeep & Senetakis, , ) showed that the theoretical curves plotted using the Hertz model fit the experimental data reasonably well apart from an initial regime where the behavior is elastic‐plastic to plastic for rough surface morphologies.…”
Section: Contact Mechanics Modelsmentioning
confidence: 78%